(untitled) (Revista Científica Compendium, 2021)
This article analyzes the working conditions of hotel workers in the Chapultepec-Polanco, area of Mexico City, which determines the levels of flexibility and job precariousness based on three dimensions: the economic one, the regulatory one, and job security. It is a quantitative, cross-sectional, non-experimental study that, through a self-administered questionnaire, shows the conditions that prevail in the tourism work of the hotel industry in the different operational, administrative and managerial areas. Factor analysis was used to identify the different existing levels of precariousness (high, medium and low). The results show that companies fulfill payment obligations established by law. However, there are high levels of precariousness due to the salaries the workers receive, the positions they occupy and the working hours, to name a few. Therefore, hotels must consider that working conditions are not strictly imposed obligations, but they must be observed as actions that increase the quality of life at work.